Pengaruh Etika Profesionalisme dan Kepatuhan pada SOP Terhadap Kinerja Pegawai dengan Disiplin Kerja sebagai Variabel Intervening pada Pengadilan Negeri Tanjung Pati - Aulia Alfacrisy; Anne Putri (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Professional human resources, compliance with procedures, and high work discipline are the main keys to achieving optimal organisational performance, including in the Tanjung Pati District Court. Problems related to professional ethics, compliance with SOPs, and employee discipline indicate the need for further analysis to determine the influence of these factors on employee performance as a whole. This study aims to analyse the influence of professional ethics and compliance with Standard Operating Procedures (SOPs) on employee performance, with work discipline as an intervening variable at the Tanjung Pati District Court. The study was conducted at the Tanjung Pati District Court with a sample of 42 respondents. The method used is a quantitative approach with the SEM-PLS analysis technique. The results of the study indicate that professional ethics have a positive but insignificant effect on employee performance and work discipline. Conversely, compliance with SOPs is proven to have a positive and significant effect on performance and work discipline. Work discipline also has a positive and significant effect on employee performance. As an intervening variable, work discipline is unable to mediate the effect of professional ethics on performance but is able to mediate the effect of compliance with SOPs on employee performance. This finding confirms that compliance with SOPs and improving work discipline are key factors in improving employee performance in the judicial environment